Suspicion and referral of patients with transthyretin amyloid cardiomyopathy: Recommendations by a Portuguese multidisciplinary expert panel - Dulce Brito; João Agostinho; Carlos Aguiar; Sílvia Aguiar Rosa; Nuno Cardim; Cândida Fonseca; Nuno Marques; Pedro Moraes Sarmento; Patrícia Rodrigues; Jonathan Santos; Maria João Vidigal Ferreira; Olga Azevedo (Revista Portuguesa de Cardiologia)
Early diagnosis of transthyretin amyloid cardiomyopathy (ATTR-CM) is crucial for better disease management and outcome. To ensure timely diagnosis, a multidisciplinary panel of Portuguese experts, including cardiologists, internal medicine specialists, and general practitioners, have developed a national consensus to aid physicians in enhancing the referral of patients with suspicion of ATTR-CM in Portugal.A structured approach was used to develop the consensus: (1) an online survey aimed at identifying clinical red flags, patient journeys, and diagnostic tools related to ATTR-CM; (2) a face-to-face roundtable meeting where the survey findings were discussed and a consensus was reached on referral and diagnostic algorithms for ATTR-CM in Portugal; and (3) critical review of the proposed algorithms.The referral and diagnostic algorithms for ATTR-CM in Portugal were developed considering current recommendations, but also the existence of a nationwide network of specialized cardiomyopathy clinics and national reference centers for familial amyloid polyneuropathy due to the endemic p.V50M variant.This collaborative effort aims to enhance awareness, facilitate timely referrals and improve early diagnosis, ultimately ensuring better management of ATTR-CM patients in Portugal. Resumo: O diagnóstico precoce da cardiomiopatia por amiloidose de transtirretina (ATTR-CM) é fundamental para uma melhor gestão e prognóstico da doença. Para promover um diagnóstico atempado, um painel multidisciplinar de peritos portugueses, composto por cardiologistas, especialistas em medicina interna e médicos de medicina geral e familiar, desenvolveu um consenso nacional com o objetivo de apoiar os médicos no processo de referenciação de doentes com suspeita de ATTR-CM em Portugal.Foi adotada uma abordagem estruturada para a elaboração do consenso: (1) um inquérito online direcionado para a identificação de sinais de alerta clínicos, trajetórias dos doentes e ferramentas de diagnóstico de ATTR-CM; (2) reunião presencial em formato de mesa-redonda, onde os resultados do inquérito foram discutidos e se alcançou consenso sobre os algoritmos de referenciação e diagnóstico de ATTR-CM em Portugal; e (3) revisão crítica dos algoritmos propostos.Os algoritmos de referenciação e diagnóstico de ATTR-CM em Portugal foram desenvolvidos tendo em conta as recomendações internacionais atuais, bem como a existência de uma rede nacional de clínicas especializadas em miocardiopatias e centros de referência nacionais para a polineuropatia amiloidótica familiar devido à variante endémica p.V50M.Este esforço colaborativo visa aumentar a sensibilização, facilitar a referenciação atempada e melhorar o diagnóstico precoce, assegurando, em última instância, uma melhor gestão dos doentes com ATTR-CM em Portugal.